Molecularly Engineered Artificial Solid Electrolyte Interphase with Tailored Lithiophilicity and Solvent-Phobicity for Stable Lithium Metal Batteries - Jeong, Yeong Hun; Won, Gwangbin; Kim, Seunghyeon; Jeong, Daun; Kwon, Da-Sol; Yong, Da Kyoung; Choi, Jaehyuk; Ahn, Hyun Woo; Kim, Sulkyung; Lim, Miso; Shim, Jimin (Wiley - V C H Verlag GmbbH & Co., 2025)
Lithium (Li) metal is recognized as a promising anode material for rechargeable batteries primarily due to its high specific capacity and energy density. However, a major challenge persists in uncontrolled Li electrodeposition and irregular solid electrolyte interphase (SEI) formation during cycling, leading to premature cell failure and safety hazards. Herein, an artificial SEI is presented for Li metal with tailored lithiophilicity and solvent-phobicity to address these critical issues. As a model system for the artificial SEI, a series of polyethyleneimine (PEI) substituted by 1,2-epoxyhexane (EH) (PEI-EH) is introduced, consisting of lithiophilic, nitrogen-rich PEI, which promotes Li ion solvation and regulates uniform ion flux. The abundant amine groups in PEI are partially substituted with solvent-phobic hexyl groups to reduce electrolyte swelling and prevent solvent decomposition. By systematically modulating the physical properties of PEI-EH, including polarity and mechanical characteristics, an optimized artificial protective layer for Li metal that effectively suppresses Li dendrite growth and irregular SEI formation is identified. This study highlights the importance of molecular engineering in the design of artificial SEIs for achieving dendrite-free, long-lasting Li metal batteries.